Phantoms of remembrance : memory and oblivion at the end of the first millennium - Geary, Patrick J., 1948- (ACLS Humanities E-Book., 1994)
In Phantoms of Remembrance, Patrick Geary makes important new inroads into the widely discussed topic of historical memory, vividly evoking the everyday lives of eleventh-century people and both their written and nonwritten ways of preserving the past. Women praying for their dead, monks creating and re-creating their archives, scribes choosing which royal families of the past to applaud and which to forget: it is from such sources that most of our knowledge of the medieval period comes. Throughout richly detailed descriptions of various acts of remembrance--including the naming of children and the recording of visions--the author unearths a wide range of approaches to preserving the past as it was or formulating the past that an individual or group prefers to imagine.